Pesantren Education as Indonesia's Indigenous Heritage: Nurturing Moral Education in the Digital Era - Cahyono Cahyono; Loso Judijanto; Erik Saut Hatoguan Hutahaean; Ulfatun Wahidatun Nisa; Mulyadi Mulyadi; Hosaini Hosaini (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2024)
Pesantren as Indonesia's original educational institution has proven to produce experts in their fields for hundreds of years. The current modern higher education system often does not prioritise the formation of ideal human beings, but is more focused on the formation of material-oriented individuals who lack spiritual values. This problem demands serious efforts in strengthening the peace and tranquillity of life, both through escorting and developing human resources, as well as through a revolution in the performance of educators and the higher education system as a whole. This research aims to see how Pesantren Education as Indonesia's Indigenous Heritage: Nurturing Moral Education in the Digital Era and its Human Resources have the capability to manage and survive in the current digital era. This research method is qualitative and quantitative, where the author uses literature studies and case studies that take place at Pondok Modern Darussalam Gontor, which is a representation of pesantren that have superior universities in Indonesia. The results of this study are In this model, character education, career development and performance improvement of Islamic human resources, Islamic human resource development, and Pondok Modern Darussalam Gontor become an important part of the programmes offered. In addition, the programme also includes values such as Qurrota A'yun, Islamic human resource development, sincerity, independence, modernity, leadership and success in the Islamic context, boarding school, simplicity, and culture and structure. Gontor endeavours to create a learning environment that conforms to the principles of the Islamic learning model for human resource development and Islamic values become the main guideline in human resource management, while career development based on Islamic law is also prioritised to form quality Islamic human resources. Aspects of Islamic professionalism are also emphasised to ensure the integration of Islamic values in professional actions and behaviour.